THE FORMATION OF THE FEMINIST MARCH: ANALYSIS OF INTERNATIONAL AND KAZAKH EXPERIENCE (The Journal of Psychology and Sociology, 2023)
The article examines the process of formation of the women's movement through the prism of international and Kazakh experience of feminist marches. The purpose of the study is a comparative analysis of national and foreign practices of feminist marches for a better understanding of the processes of formation of the women's movement in Kazakhstan. The article describes four high waves of the feminist march during its appearance. At the same time, comparing the experience of the Kazakh and foreign women's March, questions were raised about the cautious attitude towards feminist movements in connection with the policy of a particular country, as well as in ensuring women's rights.The methods of historical and comparative analysis, in-depth interviews and questionnaires were used as the methodological basis of the study. This made it possible to reveal the history of the development of the foreign and Kazakh feminist march, its common and distinctive features related to the politics of various states, and the interview method allowed to obtain information about the current state of feminism in Kazakhstan and the problems of organizing the march.According to the results of the research, the authors conclude that only the feminist movement has constantly and systematically defended the rights of women since its inception, and the effectiveness of the movement (in particular, the provision of economic, civil and political rights to women at the present time and at the beginning of the twentieth century, primarily suffrage) was that the feminist movement played an important role in social and political life. The analysis also showed that the organization of Kazakhstan feminist marches did not have full support from the political authorities and obtaining permission to hold marches requires great effort and painstaking work. The practical significance of the study is determined by the fact that the conclusions obtained in the study can be used in the work of women's socio-political organizations, in the preparation of courses in national history, political science and sociology on the history of the women's movement.Key words: gender, feminism, feminist march, women's movement, international experience, politics.